Identidade, manifestação e repressão entre os aqueus (Tersites na Ilíada, Canto 2) - Frade, Gustavo (Classica - Revista Brasileira de Estudos Clássicos, 2024)
Unlike all the other warriors in the Iliad, who are identified by their lineage or their region of origin, Thersites is not introduced as a representative of any land, nor is he presented as the son of anyone. In the absence of an explicitly defined identity and social position, Thersites is characterized initially by the peculiarities of his speech and shortly thereafter by his unique appearance. Thersites’ social position, however, is not evident in the poem. The purpose of this text, therefore, is to understand the episode of Thersites and his characterization by examining the narrative context in which the character appears (the Diapeira, the test of the army), then to recover his identity by comparing the Iliad with other ancient sources of traditional stories about the Trojan War. This will lead us to interpret his speech in light of the violent response he receives. The characterization of Thersites, which integrates him in a peculiar way into this poetry that sings of memorable deeds worthy of praise, is part of his traditional narrative function of reproving and being reproved. The Iliad, however, omits Thersites’ aristocratic origins in order to dissociate his negative physical and moral traits from the warrior aristocracy.